Evaluation of the Role of UNDP in Supporting National Achievement of the Millennium Development Goals - United Nations Development Programme (United Nations, 2015)
The evaluation of the role of UNDP in supporting national achievement of the Millennium Development Goals (MDGs) is an independent thematic evaluation conducted by the Independent Evaluation Office (IEO) of the United Nations Development Programme (UNDP) in 2014. The evaluation focuses on the tools and initiatives provided by UNDP in support of government and civil society efforts to fulfil the Goals, including national reports, advocacy (Millennium Campaign), inclusion innational development strategies and poverty reduction strategies, costing exercises, the Millennium Development Goals acceleration framework, localizing the Goals, etc.